2020
DOI: 10.1002/imhj.21867
|View full text |Cite
|
Sign up to set email alerts
|

The “EA brief”: A single session of parent feedback and coaching to improve emotional attachment and emotional availability (EA)

Abstract: The goal of this study was to determine the extent to which a brief parenting intervention provided the context for helping families to support positive motherchild interactions as well as more optimal mother and child outcomes. Participants in this study were middle income mothers and their children were between 0-3 years of age (N = 25 dyads). Participants were filmed via Skype during a 20-minute mother-child free play and completed questionnaires (Time 1) before attending the brief intervention (involving: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…This was the case, also for adopted children, in an EA parent intervention, but not in a control group (Baker et al, 2015) and for both children (child responsiveness) and teachers (structuring) in an EA child care intervention, also compared to a control group (Biringen et al, 2012). In a recent study with a brief parenting intervention with only one session for middle class mother-child dyads from 0 to 3 years (McConnell et al, 2020), only the child dimensions showed significant improvement. In an attachment-based intervention study with multi-cultural, pregnant adolescents in Australia (Nicolson et al, 2013) the intervention group scored significantly higher than the comparison group in two subscales (maternal non-intrusiveness and maternal non-hostility) in a free play situation and additionally in maternal sensitivity in a free play plus separation-reunion setting.…”
Section: Introductionmentioning
confidence: 91%
“…This was the case, also for adopted children, in an EA parent intervention, but not in a control group (Baker et al, 2015) and for both children (child responsiveness) and teachers (structuring) in an EA child care intervention, also compared to a control group (Biringen et al, 2012). In a recent study with a brief parenting intervention with only one session for middle class mother-child dyads from 0 to 3 years (McConnell et al, 2020), only the child dimensions showed significant improvement. In an attachment-based intervention study with multi-cultural, pregnant adolescents in Australia (Nicolson et al, 2013) the intervention group scored significantly higher than the comparison group in two subscales (maternal non-intrusiveness and maternal non-hostility) in a free play situation and additionally in maternal sensitivity in a free play plus separation-reunion setting.…”
Section: Introductionmentioning
confidence: 91%
“…There were no measurements of observed EA or of objectively measured sleep indicators, such as actigraphy. An additional two studies have shown that the EA-SR improves after intervention with direct coaching about attachment, EA, and use of mindfulness exercises (Baker et al, 2015;McConnell et al, 2020). Baker et al (2015) work was with 0-5-year-olds and McConnell et al ( 2020) studied 0-3-year-olds.…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…However, unlike Marte Meo, this method appears to be able to create improvement for those with mild interactional issues. McConnell et al (2020) conducted a single session of video feedback used for parent coaching for mothers of children 0-3 years of age, combined with the delivery of information (via one workshop that included coverage of mindfulness, attachment, and EA as well as sharing of videos of other parents) and 14 days of texting about attachment, mindfulness, and EA, referred to as the three pillars of practice. There was no control group.…”
Section: Prevention and Intervention Effortsmentioning
confidence: 99%